Peran Gaya Kepemimpinan dan Motivasi Dalam Meningkatkan Kinerja Karyawan pada PT Jsky Energy Indonesia - Ayu Novita Sari; Mega Puspita Sari (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the role of leadership style and motivation in improving employee performance at PT Jsky Energy Indonesia. This research uses qualitative descriptive research methods. Respondents in this study were 10 respondents consisting of contract and daily employees consisting of leaders, raw materials, QC and operators of PT Jsky Energy Indonesia. The data collection methods used are observation, interviews and documentation. The data collected is analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of this study indicate that the Role of Leadership Style and Motivation in Improving Employee Performance of PT. Jsky Energy Indonesia is very good as evidenced by unhurried decision making and through consideration, leaders always motivate employees, leaders often communicate with employees, leaders give instructions or orders to employees so that employees can work properly and correctly, leaders always carry out their duties and obligations seriously and responsibly, leaders can control their emotions, leaders not only see production progress from reports but go directly to the field, leaders have a future orientation so that PT. Jsky Energy Indonesia always innovates to create new quality products, leaders have a high level of ideals so that PT. Jsky Energy Indonesia always strives to be a better company than its competitors, leaders have task orientation and task seriousness with frequent leaders always controlling and ensuring conditions in the field, efforts to progress made by leaders by providing innovations in improving product quality, leaders have work diligence by often doing work outside office hours, always ensuring the state of production is running well, leaders have good relationships with coworkers, and leaders can utilize their time well and maximally. Keywords: Leadership Style, Motivation, Employee Performance